THE WORD SHAME IN PROVERBS - Jurayeva Manzura Yunusaliyevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article offers an in-depth linguistic and cultural analysis of the concept of shame in the English language. Drawing upon lexicographical sources, idiomatic expressions and English proverbs, the study examines how shame is both emotionally experienced and linguistically expressed. The work explores the evolution of the lexeme "shame", tracing its semantic meanings such as guilt, disgrace, embarrassment, and moral failure. A central focus is placed on how shame is encoded in 17 English proverbs, which reflect the values, moral codes, and behavioral expectations of Western society.